Emergency surgical treatment of total anomalous pulmonary venous connection. Issue 1 (20th October 2021) - Wu, Yongtao; Fan, Xiangming; Chen, Li; Wang, Dong; Su, Junwu; Jin, Can; Wang, Zhiyi
Abstract: Background: This study explored the strategy and effect of emergency surgical treatment for total anomalous pulmonary venous connection (TAPVC). Methods: From March 2009 to February 2020, 78 patients with TAPVC underwent emergency surgical correction. There were 51 males and 27 females. The median age was 39.5 days, and the median weight was 4.0 kg. Preoperative percutaneous oxygen saturation was 80.8% ± 4.5%. Results: Of the cases investigated, seven died during the perioperative period; 16 had a delayed chest closure; 19 had early pulmonary vein obstruction; two had secondary tracheal intubation; one had a brain complication; and one had a third‐degree atrioventricular block. Low weight, younger age, cardiopulmonary bypass time, and aortic cross‐clamp time were identified as risk factors for early mortality. During the follow‐up from 4 to 137 months, 12 cases did not respond to follow‐up requests. Ten patients died within 1–6 months after discharge. One patient underwent reoperation due to pulmonary vein obstruction. The longer hospital stay after the operation and intensive care unit time were identified as risk factors for late mortality. Conclusions: Emergency surgery for severe TAPVC patients after admission achieved good short‐term results. Prenatal diagnosis should be strengthened to save more patients. The higher late mortality rate of such patients indicates that post‐discharge management should be strengthened to reduce the occurrence of post‐discharge deaths.